Strategic Marketing Approach and Innovation in Sam Antep Gilam Carpet Company - Oblakulov , Bekzodjon (Academia Open, 2025)
General Background: The global carpet industry continues to evolve amid rising consumer expectations for quality, sustainability, and innovation. Specific Background: SAG Carpet Company, a market leader in Uzbekistan, integrates traditional craftsmanship with modern production to offer high-quality carpets, artificial grass, and agricultural exports. Knowledge Gap: Despite its market presence, limited studies analyze how such heritage-based firms adopt strategic marketing frameworks in competitive international contexts. Aims: This study aims to evaluate SAG's comprehensive marketing strategy using SWOT, BCG Matrix, Marketing Mix (4Ps), and its dual-market (B2B and B2C) approach. Results: The analysis reveals that SAG's strengths lie in its vertically integrated production, diversified portfolio, and expanding global footprint. However, it faces challenges from increasing competition and shifting consumer trends. Novelty: This paper contributes by aligning traditional manufacturing values with digital transformation strategies, including smart carpet innovation, augmented reality retailing, and value-based pricing. Implications: The findings highlight strategic pathways for similar firms to sustain competitiveness by balancing cultural authenticity with technological advancement, offering insights for practitioners in emerging economies seeking global market integration. Highlights: Highlights SAG's integration of tradition and innovation in global marketing. Emphasizes strategic use of 4Ps and segmentation for market expansion. Recommends digital transformation to sustain competitive advantage. Keywords: Marketing Strategy, SAG Carpet Company, SWOT Analysis, BCG Matrix, Value-Based Pricing